OXPHOS remodeling in high-grade prostate cancer involves mtDNA mutations and increased succinate oxidation - Schöpf, Bernd; Weissensteiner, Hansi; Schäfer, Georg; Fazzini, Federica; Charoentong, Pornpimol; Naschberger, Andreas; Rupp, Bernhard; Fendt, Liane; Bukur, Valesca; Giese, Irina; Sorn, Patrick; Sant’Anna-Silva, Ana Carolina; et al. (Nature Communications, 2020)
The re-wiring of the metabolic machinery is a common feature in cancer. Here, the authors show, using paired normal and prostate cancer samples that the cancer samples exhibit a shift to succinate respiration, which is associated with elevated levels of mitochondrial DNA mutations.